EFEKTIVITAS POSITIONING JURUSAN MANAJEMEN DAN PENGARUHNYA TERHADAP TINGKAT KEPUASAN (SATISFACTIONS) JASA PELAYANAN (STUDI PADA PERGURUAN TINGGI SWASTA DI BANDARLAMPUNG) - Anuar Sanusi (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2013)
This study aimed to determine the effectiveness of the formation of public perceptionmanagement majors (positioning) through marketing strategies (product, promotion, place, priceprocesses, people, services and the level of satisfaction). The results showed that the sequence ofthe highest variable shape their effectiveness is variable positioning process, variable service,variable space, variable pricing, promotion variable. Whereas variable ineffective cover variables,and variable products/ graduates. Variable attributes of brand loyalty in the visible frequencyattributes in the sense that like the education (frequency) assessed by a variation less often quitehigh, but it will not reduce the assessment of the service received, for services providedmanagement department meets department higher standards set. While others attribute torecommend to the comfort (comfortable) and preferences with services obtained got a pretty goodassessment, while the other attributes that tend to get a very good assessment of the variation isalmost the same. Attributes related to the service, is the most influential variable, and the mostimportant factors to changes in loyalty management majors existence and Attributes related to thepurchase of statistical models that also affect positively to the presence of the managementdepartment.